THE INFLUENCE OF DA’I PERSONALITY AND DA’WAH BIL HAL TOWARDS SPIRITUAL MOTIVATION OF MAD’U - Farmawati, Cintami (JURNAL MANAJEMEN DAKWAH, 2017)
A da’i must have a good personality when entering the field of da’wah so as to move or spur the mad’u to arise awareness in performing charity and that the goal of da’wah can be achieved. This study aims to explain effect of da’i personality and da’wah bil-hal towards spiritual motivation of mad’u. Its population is all mad’u and da’i in Boarding School of Bahrul Ulum of Pemalang Regency. The sample in this study is 77 mad’u which is divided into 35 people (45,5%) women and 42 people (54,5%) men. As for the entire population of da’i is used as a sample, which is 4 da’i. Sampling technique used is nonprobability sampling. The measuring tools used are personality scale, bil-hal da’wah scale, and spiritual motivation scale in the form of Likert. The data analysis used is Multiple Regression Analysis at 0.05 significance level. The results showed that there was a significant effect of da’i personality and da’wah bil-hal towards spiritual motivation of mad’u. The variables that show the most dominant positive tendencies and significantly influence the spiritual motivation of mad’u are the personality of extraversion, openness to experience, agreeableness, religious, education, organization and social.